WEST LYNN RESIDENCE. - I. V. (Architect)
The West Lynn Residence in Austin, Texas, is a Georgian Revival house that has been renovated and adapted by A Parallel Architecture. The designers preserved the traditional living spaces while giving them a more open and airy feel. They also added a new glass and brick addition to the house, creating opportunities for indoor-outdoor socializing. The combination of the old and new elements creates a visually striking and complementary pairing. The design of the house incorporates craftsmanship and blends in with the surrounding trees.